Synergy of Systems, Strategy, and Culture : Examining the Determinants of Financial Report Quality in the Public Sector - Risa Mayasari (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to examine the influence of Accounting Information Systems (AIS), Internal Reporting Strategies (IRS), and Organizational Culture (OC) on the Quality of Financial Reporting (QFR) in public sector organizations in East Java, Indonesia. The quality of financial reports serves as a crucial indicator of transparent and accountable public governance. However, many local governments continue to face persistent challenges in producing reliable financial statements, primarily due to limitations in information systems, weak internal reporting controls, and organizational cultures that have not fully embraced the principles of good governance. A quantitative approach with a descriptive-verificative research design was employed. Data were collected through a structured questionnaire distributed to financial management personnel in local government institutions and analyzed using Structural Equation Modeling based on Partial Least Squares (PLS-SEM). The findings reveal that all three independent variables—AIS, IRS, and OC—have a positive and statistically significant impact on QFR, with a high predictive contribution (R² = 0.804). AIS plays a critical role in enhancing the accuracy and efficiency of financial reporting, IRS strengthens internal control mechanisms and compliance, while OC fosters organizational behaviors that uphold integrity and accountability. In conclusion, improving the quality of financial reporting in the public sector requires a holistic approach that integrates robust information systems, effective internal reporting strategies, and an organizational culture that supports transparent and ethical reporting practices.